Combined strategy for 17-α-ethynilestradiol removal, CO2 fixation, and carotenoid accumulation using Thermosynechococcus sp. CL-1 cultivation. (May 2023) - Narindri Rara Winayu, Birgitta; Tsai, Sheng-Bin; Hsueh, Hsin-Ta; Chu, Hsin
Abstract: An isolated cyanobacterium, Thermosynechococcus sp. CL-1 (TCL-1), is a potential CO2 fixation, estrogen removal, and pigments production agent even under extreme conditions. In this study, TCL-1 was cultivated under various 17-α-ethinylestradiol/EE2 contents and growth conditions (light intensities and dissolved inorganic nitrogen/DIN). Under low EE2 concentration (1 mg/L), TCL-1 presented hormesis phenomenon with promotion of biomass productivity (68.2 ± 0.6 mg/L/h) and β-carotene productivity (0.47 ± 0.12 mg/L/h) compared to control cultivation without EE2. Strong endurance of TCL-1 was indicated by insignificant biomass growth reduction, even under 10 mg/L EE2. Moreover, compared to the variety of DIN levels, light intensity presented a greater influence on growth, CO2 fixation, and carotenoid accumulation of TCL-1. Total EE2 removal by TCL-1 reached the range of 66.4–82.3 % and the process was initiated by adsorption on cells' surfaces prior to accumulation. Graphical Abstract: ga1 Highlights: TCL-1 growth was stimulated by the presence of 1 mg/L of EE2 due to biphasic effect. The best EE2 removal of 82.3 ± 6.5 % was achieved by TCL-1 under addition of 1 mg/L EE2. Higher light intensity promoted CO2 fixation rate and EE2 degradation. TCL-1 dominantly produced β-carotene as the accumulated carotenoid.